PENDIDIKAN PRE-NATAL DALAM TAFSIR TARBAWI UNTUK MEMBENTUK INSAN KAMIL - Muhammad Gus Nur Wahid; Muhamad Rudi Wijaya; Subekti (Journal of Islamic Education and Learning, 2021)
This pre-natal period occurs from the start of fertilization of the sperm to the egg until birth, normally this period lasts according to the average gestational age in general, which is around nine months. Pre-natal education to form human beings insan kamil is to interpret Nur Nabi Muhammad SAW, as the source of Akhlakul Karimah, but must be adapted to the conditions of the essence and soil, therefore good habits are needed. According to the Qur'an several verses relating to the responsibility of education are Qs: At-Tahrim (66): 6, QS. Al-Isra (17): 31, Qs. Al-Anam. (6): 151, Qs. At-Taubah (9) : 122. Qs. Al-A'raf (7): 179, Qs. Ali-Imran, (3): 104, QS. Al-Isra (17): 36, Qs. Ali-Imran, (3): 191, Qs. Al-Furqan (25): 74, and Qs. Al-Baqarah (2) : 128.